Necropolitical Education:: Authoritarian Personality, Violence and Schooling of Poor Young People in Brazil - Chaveiro, Eguimar Felício; Almeida, Rosivaldo Pereira de (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The article is an explanatory summary of the discussions made in the course "Necropolitical Education in the context of fascism" offered in the context of the pandemic by the Nucleus of Human Rights, Education and Social Movements of the State University of Goiás (NUDHEM/UEG), Study Group Space, Subject and Existence Dona Alzira of the Federal University of Goiás and the National Movement of Human Rights (MNDH). The work addresses the relational character of necropolitics with education and discusses its fundamentals: Authoritarian personality, physical and symbolic violence and the objective and subjective mechanisms of elimination of poor young people in the processes of schooling. We consider the educational dimension and the necrophilous character of the debris and captures of the subjectivities present in the schooling processes. The theoretical references that underpin our analysis are Mbembe (2012), Adorno (1951), Rolnik (2018) and Bourdieu (1998).